2004
DOI: 10.1039/b312558k
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in rainwater in Flanders, Belgium: results from the monitoring program 1997–2001

Abstract: In 1997 the Flemish Environmental Agency (FEA) started a monitoring program "Pesticides in Rain in Flanders, Belgium". The original purpose of the monitoring program was to examine the possible occurrence of dichlorvos in rainwater and subsequent deposition. However, it was thought necessary from the beginning to monitor a wide range of pesticides. During the first year some 62 pesticides and metabolites and 9 polychlorinated biphenyls, were monitored at 4 locations. Nowadays the monitoring program has grown u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 18 publications
3
23
1
3
Order By: Relevance
“…Figure 7 shows that concentrations increased from January to March, which are the months with more intensive pesticide application. Our results corroborate the ones found by Lourencetti et al 43 who, similarly, detected β-endosulfan, endosulfan sulfate, metolachlor, Some of these pesticides were also detected by Quaghebeur et al 44 who initiated a pesticide monitoring study in rainwater in Flandres, Belgium. The authors observed that the most frequently detected ones were α, β-endosulfan and endosulfan sulfate, atrazine, diuron, glyphosate and isoproturon from 1997 to 1999.…”
Section: Pesticides In Rainwatersupporting
confidence: 82%
See 1 more Smart Citation
“…Figure 7 shows that concentrations increased from January to March, which are the months with more intensive pesticide application. Our results corroborate the ones found by Lourencetti et al 43 who, similarly, detected β-endosulfan, endosulfan sulfate, metolachlor, Some of these pesticides were also detected by Quaghebeur et al 44 who initiated a pesticide monitoring study in rainwater in Flandres, Belgium. The authors observed that the most frequently detected ones were α, β-endosulfan and endosulfan sulfate, atrazine, diuron, glyphosate and isoproturon from 1997 to 1999.…”
Section: Pesticides In Rainwatersupporting
confidence: 82%
“…Moreover, these authors reported that the frequency of detection was related to local pesticide pulverization. 44 In contrast, Murti and Nag 45 (in a study involving ten European countries) observed that some of the pesticides monitored were not used on the agricultural areas where the rain samples were collected, indicating long distance transport of these compounds in the atmosphere.…”
Section: Pesticides In Rainwatermentioning
confidence: 99%
“…Therefore, the ratio should consider not only the amount applied but also the amount accumulated from previous treatments. Recent experimental and monitoring studies confirm wind-driven transport of glyphosate and AMPA (Bento et al, 2017;Farenhorst et al, 2015;Lamprea and Ruban, 2011;Quaghebeur et al, 2004). Bento et al (2017) demonstrated in a wind tunnel experiment that contents of AMPA and especially of glyphosate were particularly high (respectively N 0.6 and N 15 μg g −1 ) in the finest soil particle fractions (b 10 μm), which can be inhaled by humans directly.…”
Section: Off-site Transport By Wind and Water Erosionmentioning
confidence: 99%
“…, respectively (Quaghebeur et al, 2004). Glyphosate is supposed to degrade rapidly in the atmosphere by photochemical oxidative degradation (EFSA, 2013), but the results from air and rain analyses indicate that glyphosate and AMPA can persist in the atmosphere and can be washed out and redistributed by rain (wet deposition).…”
Section: Off-site Transport By Wind and Water Erosionmentioning
confidence: 99%
“…For example, Wilson (2012) calculated that the mass of glyphosate applied in the Province of Manitoba far exceeds that of any other pesticide used. In bulk deposition studies conducted in rural areas of the Prairies (Chang et al, 2011;Humphries et al 2005;Messing et al, 2011;Quaghebeur et al, 2004), glyphosate was detected in 50 to 92% of the samples. Other herbicides that have been frequently detected in deposition samplers deployed in rural areas of the Prairies are 2,4-D, bromoxynil, dicamba and MCPA (Hill et al, 2003;Messing et al 2011;Rawn et al, 1999;Waite et al, 2005).…”
Section: Introductionmentioning
confidence: 99%